Concerns of pregnant women and women in childbed during the pandemic - Tułacz, Kinga; Wierzbicka, Barbara; Berghausen-Mazur, Marta (Nursing in the 21st Century, 2021)
CONCERNS OF PREGNANT WOMEN AND WOMEN IN CHILDBED DURING THE PANDEMIC Aim. The purpose of the paper was to determine the type of concerns of pregnant women and women in childbed during the announced state of pandemic in the country. Material and methods. The study included a group of 102 women, including 87 (85.3%) pregnant women and 15 (14.7%) puerperal women. A self-written questionnaire containing 18 questions was used for the study. The comparison of the values of the qualitative variables in the groups was performed using the chi-square test or Fisher’s exact test. The statistical analysis was performed in the R program, version 4.0.2. Results. In the study group, the respondents’ greatest fear was childbirth without an accompanying person. A frequent cause of concern among the respondents was the limitation of follow-up visits to the doctor or midwife providing prenatal care. Limited physical activity during the pandemic also turned out to be a significant concern. Only 11.8% of the respondents did not feel any fear in their current pregnancy. Additionally, among the reasons for their concerns, the respondents mentioned, among others: fear of separation of mother and child after delivery, the need to care for an older child, no visits to specialists, fear of infection with SARS CoV-2 virus. Statistical analysis confirmed a significant correlation between the number of children already owned and the concerns of pregnant women regarding being resourceful in caring for themselves and their child after returning home. Conclusions. The duration of the pandemic is a significant stress factor for a pregnant woman. A significant group of female respondents was concerned about the deterioration of maternity care and infection with the virus during hospital stay. Therefore, the task of medical personnel is to provide mental support and educate patients.